2020
DOI: 10.3390/ijerph17207538
|View full text |Cite
|
Sign up to set email alerts
|

Snacks and The City: Unexpected Low Sales of an Easy-Access, Tasty, and Healthy Snack at an Urban Snacking Hotspot

Abstract: : While many people declare an intention to eat and snack more healthily, a large body of research has found that these intentions often do not translate into actual behavior. This failure to fulfil intentions is regularly attributed to the obesogenic environment, on which basis it is assumed that changing the food environment may lead to more healthy snacking behavior. To test this premise in real life practice, the present research project investigated whether making a healthy snack easy-to-access in an urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Women have more preference than men to buy snacks in supermarkets and self-service stores, in markets, and prepared at home (p0.05). Schlinkert et al, 2020 reported that young people in the Netherlands went to snack outlets, as a result, levels of obesity and overweight increased. However, they are snacking at home (58%), at work, or at school (23%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women have more preference than men to buy snacks in supermarkets and self-service stores, in markets, and prepared at home (p0.05). Schlinkert et al, 2020 reported that young people in the Netherlands went to snack outlets, as a result, levels of obesity and overweight increased. However, they are snacking at home (58%), at work, or at school (23%).…”
Section: Resultsmentioning
confidence: 99%
“…Some examples of snacks are cookies, cakes, sugar-sweetened beverages, and chips. Recent studies also indicate that legume flour can be incorporated into snacks instead of cereals, significantly improving their functional properties and their nutritional value (Szymandera-Buszka et al, 2021). Legumes are highly beneficial in the diet of people, due they have considerable quantities of water-soluble vitamins, minerals, and bioactive ingredients such as polyphenols, essential amino acids, fibers, and proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies highlight that the "healthiness" of a food is usually not a relevant criterion in the choice of purchasing snacks. For these foods, parameters such as palatability, price, convenience and brand seem to be more important [49][50][51][52]. This would explain why the Nutri-Score appears to not have a significant impact on snack choices [12].…”
Section: The Impact Of Fopls On Food Choice and Consumer Behaviormentioning
confidence: 99%
“…Stimulating healthy snack choice is important as snacking tends to involve the consumption of food of poor nutritional quality ( Larson and Story, 2013 ), and is associated with unhealthy diet and obesity ( Forslund et al, 2005 ). Because snacks are predominantly consumed at home (e.g., Kerr et al, 2010 ; Myhre et al, 2015 ; Schlinkert et al, 2020 ), decisions made in the supermarket largely define the snacks people end up consuming ( Papies et al, 2014 ), deeming the supermarket a relevant location to nudge healthier snack choices.…”
Section: Introductionmentioning
confidence: 99%